Narsisme Dalam Menyusun Laporan Keuangan: : Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2023 - Setiajatnika, Eka; Nugraha, Heri; Gunadi, Trida (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Financial reports serve as a key tool in economic decision-making, but can be influenced by psychological factors such as narcissism, which has the potential to change the way reports are prepared to highlight company performance. This study examines the influence of narcissism on the preparation of financial statements in five large manufacturing companies listed on the IDX, namely PT Astra International Tbk, PT Unilever Indonesia Tbk, PT Gudang Garam Tbk, PT Indofood CBP Sukses Makmur Tbk, and PT Semen Indonesia Tbk, during the period 2022-2023. The purpose of this study is to analyze whether narcissism affects the preparation of financial statements, as well as identify signs of narcissism in reports that can affect stakeholder perceptions. The study used quantitative methods by analyzing secondary data in the form of annual reports and company finances, and using regression to measure the relationship between narcissism and financial report quality. The results show that narcissism does have the potential to influence the preparation of financial reports, which is related to efforts to improve the company's image. This finding is important to remind companies of the importance of transparency and ethics in financial reports, in order to maintain the integrity of information provided to stakeholders.